The Activities and Secretion of Cytokines Caused by Delamanid on Macrophages Infected by Multidrug-Resistant Mycobacterium tuberculosis Strains - Lyu, Xia-Li; Lin, Ting-Ting; Gao, Jing-Tao; Jia, Hong-Yan; Zhu, Chuan-Zhi; Li, Zi-Hui; Dong, Jing; Sun, Qi; Shu, Wei; Pan, Li-Ping; Zhang, Zong-De; Li, Qi (Frontiers in Immunology, 2021)
Background Delamanid (Dlm) is an effective drug against drug-susceptible and drug-resistant Mycobacterium tuberculosis strains, including Multidrug-resistant Mycobacterium tuberculosis (MDR-MTB). There are few reports on the activity and secretion of cytokines caused by Dlm on macrophages infected by MDR-MTB strains. Therefore, this article aims to observe the bactericidal activity and secretion of cytokines of the macrophages infected by MDR-MTB strains after Dlm was administered, so as to provide a basis for further perfecting the mechanism of Dlm. Methods Samples were respectively collected to count the intracellular colony-forming unit (CFU) of macrophages infected by MDR-MTB or H37Rv strains at 4, 8, 24, and 48 h after Dlm at MIC, 10MIC, and 20MIC were administered. Samples were respectively collected to detect the level of IL-12/23 p40, TNF-α, IL-6, and IL-10 in the culture supernatant of macrophages infected by MDR-MTB or H37Rv strains at 4, 24, and 48 h after Dlm at MIC were administered. The levels of four cytokines in the culture supernatant were measured using the Luminex® 200™ (Luminex, USA) according to the manufacturer’s instructions. Data were analyzed by SPSS 25.0 software. The continuous data in normal distribution were expressed as mean ± standard deviation (x¯ ± s) and analyzed by t or F test. P<0.05 was considered statistically significant. Results (1) After Dlm was applied to macrophages infected by MDR-MTB strains: (A) The intracellular CFU gradually decreased, reached the lowest value at 48 h, and was lower than that of Dlm before administration and infection group (P<0.05). (B) The intracellular CFU was further reduced after increasing Dlm dose to 10MIC and 20MIC, and the latter was lower than that of the former (P<0.05). (C) The intracellular CFU of MDR-MTB group was higher than that of H37Rv group at 4~48 h after administration (P<0.05). (2) After Dlm at MIC dose was applied to macrophages infected by MDR-MTB strains: (A) The level of IL-12/23 p40 at any time didn’t change compared with that of Dlm before administration (P>0.05), while the level of IL-12/23 p40 at 4 h was higher than that of the infection group (P<0.05). The levels of TNF-α at 24 and 48 h were higher than that of Dlm before administration (P<0.05), but were similar to that of the infection group (P>0.05). In addition, the levels of IL-12/23 p40 and TNF-α at any time were similar to that of the H37Rv group after administration (P>0.05). (B) The levels of IL-6 at 24 and 48 h were higher than that of Dlm before administration (P<0.05), but were similar to that of H37Rv group (P>0.05) and were lower than that of infection group (P<0.05). The level of IL-10 at any time didn’t change compared with that of Dlm before administration (P>0.05), but was lower than that of the infection group at 4~48 h and was lower than that of the H37Rv group at 24 h (P<0.05). (C) The level of IL-12/23 p40 and IL-10 didn’t change with the change of intracellular CFU (P<0.05), while the level of TNF-α and IL-6 increased with the intracellular CFU decreasing, and the increase level of TNF-α was lower than that of the infection group (P<0.05). Conclusions Dlm had strong bactericidal activity against intracellular MDR-MTB, which was time-dependent and concentration-dependent. Its bactericidal activity against intracellular MDR-MTB strains was weaker than that against drug-susceptible tuberculosis strains. Dlm might have immunomodulatory effect, inducing low expression of Th2 cytokines IL-6 and IL-10 at different times after administration.